Bible and ecology rediscovering the community of creation - Bauckham, Richard 1946- (Waco, Tex Baylor Univ. Press, 2010)
Stewardship in question -- Putting us in our place -- The community of creation -- Where the wild things are -- From alpha to omega
Includes bibliographical references and index
Keywords: Human Ecology -- Biblical teaching; Human Ecology -- Religious aspects -- Christianity